Longer left ventricular activation time is associated with lower mortality and risk of heart failure hospitalization in CRT recipients. (19th May 2022) - Marinko, S; Platonov, PG; Carlson, J; Borgquist, R
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): ALF Governmental Funding within the Swedish health care system Introduction: Cardiac resynchronization therapy (CRT) is an established treatment for heart failure in selected patients. Longer QRS duration has been showed to correlate to clinical outcome, but measures global activation time, rather than the left ventricular dyssynchrony that CRT aims to correct. This study therefore evaluated the incremental value of using Left Ventricular Activation Time (LVAT) for prediction of outcome after CRT. Methods: Medical records of 445 patients receiving CRT implants at a large-volume tertiary care center were retrospectively evaluated. Digital electrocardiograms (ECG) before and after CRT implantation were collected and ECG parameters were analysed in relation to a primary composite endpoint of time to heart failure hospitalisation or death from any cause. LVAT was defined as time from QRS onset to maximum positive deflection in lead V6 (Figure 1). Results: Patients were followed for up to 6 years (median 2.7), during which 147 patients (33%) reached the primary endpoint (93 deaths and 103 heart failure hospitalisations). LVAT was measured pre-implant (median 71ms [58-88]) and post-implant (median 74ms [57-96]). There was no CRT-mediated reduction in LVAT (delta -2.3ms +/-31ms, p=0.27). When divided into quartiles, preoperative LVAT had a significant association with clinical outcome (HR 0.76 [0.64-0.90] per increasing quartile, p=0.001), also shown in a median-split Kaplan Meier curve (Figure 2, log rank p=0.001). Multivariate hazard ratio (adjusted for relevant clinical variables) was 0.83; [0.69-0.99]; p=0.047). There was an interaction between LVAT and ECG morphology (p=0.033), and when ECG groups were analysed separately, there was only a significant result for those with native left bundle branch block morphology. Post-implant LVAT, or change in LVAT, did not correlate with the primary endpoint (p=0.25 and p=0.38 respectively. Conclusion: In CRT recipients, longer pre-implant LVAT was associated with lower risk of heart failure hospitalisation and death during a follow-up of up to 6 years. This association was mainly seen in patients with native LBBB prior to implant. No association was seen with post-CRT LVAT and clinical outcome. If confirmed in prospective trials, evaluation of preoperative LVAT may help optimise patient selection for CRT.